Variable Structure Observer design for a class of uncertain systems with a time-varying delay - Liu, Wen-Jeng (Zielona Góra: Uniwersytet Zielonogórski)
Design of a state observer is an important issue in control systems and signal processing. It is well known that it is difficult to obtain the desired properties of state feedback control if some or all of the system states cannot be directly measured. Moreover, the existence of a lumped perturbation and/or a time delay usually reduces the system performance or even produces an instability in the closed-loop system.
Keywords: variable structure observer; invariance property; generalized matrix inverse approach